Où accueillir les mineurs non accompagnés en France ? Enjeux de la construction d’un territoire de protection - Sarah Przybyl (EchoGéo)
For thirty years, France has been confronted with the increasing arrival of unaccompanied minors. Under 18 years of age, they are in the territory without their legal representative. These young people are halfway between considerations for child protection and those of managing illegal immigration. Over time, more than a political problem, their very heterogeneous distribution within the French departments has become a real geographical issue. On the basis of political negotiations, this article reviews the decisions taken by the authorities to restore territorial balance and questions the place reserved for the best interests of the child.